Modification of triglyceride oil with benzoxazine functionalized silane for the purpose of oil-based binder - AYCAN, DİDEM (SPRINGER, 2020)
In the present study, a novel and easy approach for an oil-based binder production was realized by the modification of partial glycerides (PGs) with benzoxazine functionalized silane (Bz-Si) which was synthesized by the reaction between benzoxazine and 3-aminopropyltriethoxysilane. PG mixture obtained by the glycerolysis reaction was subjected to solvent extraction with methanol to concentrate PG. The enhanced partial glycerides (PGE) were thermally cured with Bz-Si. After that, the film sample cured by means of sol-gel reaction (CF(Bz-Si)/PGE) was examined in view of film properties. Applied tests showed that CF(Bz-Si)/PGE could be used as an oil-based binder for coating applications.
Keywords: Triglyceride oil; Benzoxazine; Silane coupling agent; Thermal curing; Coating; SUNFLOWER OIL; CASTOR-OIL; STYRENATION; POLYMERIZATION; POLYCAPROLACTONE; NANOCOMPOSITES; POLYMERS